Endodontic Access Cavity Designs: A Review of Traditional and Minimally Invasive Approaches - Norah Saleh Al-Houban,; Maha nasser alsharif,; Zharah kiri alhakami,; Fay abduaziz,; Munirah Ahmed abdullah alsharif,; Bashayer faris alhlail,; Dalal monief Almutery,; Lana Essa Binobaid,; Areej Muhammad Alabdullah,; Lujain megbel al habardi,; Maher Alabdulkarim,; Anwar Yahya Mashi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Endodontic access cavity preparation is a critical step that allows for straight-line access to the root canal system during root canal treatment. Traditional guidelines have called for the removal of significant amounts of tooth structure to create a straight-line access pathway. However, excessive removal of dentin can substantially weaken the remaining tooth and increase the risk of vertical root fractures. As such, there has been growing interest in minimally invasive or "conservative" access cavity designs that aim to preserve pericervical dentin and remaining tooth structure while still providing adequate access for canal instrumentation and obturation. This article reviews the current literature comparing traditional endodontic access cavities versus minimally invasive contracted access designs. It examines the impacts of these different access approaches on the efficacy of canal instrumentation and irrigation, quality of root canal fillings, biomechanical behavior, and fracture resistance of endodontically treated teeth. The potential advantages and limitations of minimally invasive cavity designs are discussed, along with emerging technologies like guided endodontics that may enable truly individualized conservative access cavities tailored to each patient's unique root canal anatomy.